Simbolisme Religius dalam Legenda Tonu Wujo Nogo Ema: Studi Etnografi pada Masyarakat Lewolema - Alfonsus Mudi Aran; Rosida Simbolon (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
This study examines the function of symbolism in the Tonu Wujo Nogo Ema legend in relation to the spiritual and social practices of the Lewolema community in East Flores Regency. The focus of this study is how this symbolism influences agricultural activities and the community's relationship with nature and God. A qualitative approach using ethnographic methods was used. Data was collected through interviews, participatory observation, and documentation. Informants were selected using purposive sampling techniques and consisted of traditional leaders, religious leaders, and young people involved in the social and ritual life of the community. Data analysis was conducted using a thematic and ethnographic approach to interpret the symbolism in the legend and its influence on the community's relationship with nature and the divine. This study shows that the Tonu Wujo Nogo Ema legend functions as a religious symbol that is manifested in daily agricultural practices, such as prayers at ceremonies before farming, during plant care, and at harvest time. This shows the connection between humans and the transcendent and immanent forces known as Rera Wulan Tanah Ekan. These results contribute to the study of religious anthropology and highlight how local symbolism shapes social and spiritual practices and their interaction with major religions such as Catholicism. The limitations of this study lie in its focus on the Lewolema community only and the lack of analysis of the impact of social change and modernity.